Cached : decoding the Internet in global popular culture - Schulte, Stephanie Ricker (Critical cultural communication., 2013)
In the 1980s and 1990s, the Internet became a major player in the global economy and a revolutionary component of everyday life for much of the United States and the world. It offered users new ways to relate to one another, to share their lives, and to spend their time: shopping, working, learning, and even taking political or social action. Policymakers and news media attempted - and often struggled - to make sense of the emergence and expansion of this new technology. This book focuses on how people imagine and relate to technology, delving into the political and cultural debates that produced the Internet as a core technology able to revise economics, politics, and culture, as well as to alter lived experience.